Comparison of haemodynamic responses to dopamine and salbutamol in severe cardiogenic shock complicating acute myocardial infarction. Issue 6257 (3rd January 1981) - Timmis, A D; Fowler, M B; Chamberlain, D A
Abstract : Twelve patients with severe persistent cardiogenic shock complicating acute myocardial infarction underwent single crossover treatment with intravenous dopamine and salbutamol to determine the more beneficial therapy. Salbutamol (10 to 40 microgram/min) reduced systemic vascular resistance and progressively increased both cardiac index and stroke index. Heart rate increased from 95 to 104 beats/min. Changes in mean arterial pressure and pulmonary artery end-diastolic pressure were small and insignificant. Dopamine infusion at rates of 200 and 400 micrograms/min also increased cardiac index and stroke index. Systemic vascular resistance fell slightly but mean arterial pressure rose from 57 to 65 mm Hg. Heart rate increased from 95 to 105 beats/min. Changes in pulmonary artery end-diastolic pressure were again small and insignificant. Dopamine infusion at 800 micrograms/min caused an appreciable increase in systemic vascular resistance; a further increment in mean arterial pressure was observed, though cardiac index fell slightly. Heart rate and pulmonary artery end-diastolic pressure rose steeply. Salbutamol, a vasodilator, increased cardiac output in patients with cardiogenic shock complicating acute myocardial infarction but did not influence blood pressure. If correction of hypotension is essential dopamine in low doses may be the preferred agent. Doses of 800 microgram/min, which is within the therapeutic range, worsen other manifestations of left ventricular dysfunction.